Chronic neck pain and depression: the mediating role of sleep quality and exercise. Issue 8 (13th September 2020) - Juan, Wang; Rui, Liang; Wei-Wen, Zhu
ABSTRACT: Previous researches have found that chronic neck pain was closely related to depression. However, the relation between chronic neck pain, sleep quality, exercise and depression remains unclear. This study aims to evaluate the association between these factors, based on the assumption that sleep quality and exercise are potential mediators in the relationship between chronic neck pain and depression. This cross-sectional study enrolled 231 patients with chronic neck pain who were referred to outpatient clinics in department of neurology between July and December 2016. Data analysis was performed using a structural equation model to evaluate the mediating effects of sleep quality and exercise frequency on the relation between chronic neck pain intensity and depression. A positive correlation between neck pain intensity and depression was unveiled. In addition, sleep quality was identified as a significant positive mediator between neck pain intensity and depression, and exercise can help relieve depression. Poor sleep quality leads to an increase of the symptoms of depression for people with high neck pain intensity which can be effectively relieved via additional exercise.